Combining unmanned aircraft systems and image processing for wastewater treatment plant asset inspection - Martínez, Jorge Sancho; Bajón Fernández, Yadira; Leinster, Paul; Rivas Casado, Monica (MDPI, 2020)
Wastewater treatment plants are essential for preserving the water quality of freshwater and marine ecosystems. It is estimated that, in the UK, as much as 11 billion liters of wastewater are treated on a daily basis. Effective and efficient treatment of wastewater requires treatment plants to be maintained in good condition. Recent studies have highlighted the potential of unmanned aircraft systems (UASs) and image processing to be used in autonomous and automated monitoring systems. However, the combined use of UASs and image processing for wastewater treatment plant inspections has not yet been tested. This paper presents a novel image processing-UAS framework for the identification of failures in trickling filters and activated sludge facilities. The results show that the proposed framework has an accuracy of 95% in the detection of failures in activated sludge assets, with the accuracy ranging between 55% and 81% for trickling filters. These results are promising and they highlight the potential use of the technology for the inspection of wastewater treatment plants
Keywords: site inspection; wastewater treatment plants; asset inspection; UASs; unmanned aircraft systems; activated sludge; trickling filters